Pelatihan Komunikasi Asertivitas Seksual Guna Mencegah Terjadinya Tindakan Seks Bebas pada Siswa SMA Negeri 1 Tanjung Mutiara Kabupaten Agam - Suci Rahma Nio; Rusli, Devi; Wibawa, Anugrah Dwi; Najwa Maharani Zahra; Sabrina Azzahra; Hesti Destri Utami; Ahmad Abrar (Universitas Negeri Padang, 2024)
Many cases of pregnancy out of wedlock and resulting in widespread early marriages indicate that the ability of children or adolescents to communicate assertively is still weak. Adolescence is a transition period not only psychologically, but also physically. This transition from child to adult includes all aspects of development experienced in preparation for entering adulthood. Assertive communication produces direct behavior that is polite and goal-oriented, a person's feelings or desires. The training in this research aims to increase the insight of students at SMA Negeri 1 Tanjung Mutiara to be better prepared to face invitations that lead to promiscuous sexual behavior by communicating assertively. The participants in this research were 50 students. The implementation is to conduct counseling first, then continue with training on how to communicate assertively. The results obtained from this training were that some students were able to practice correctly, but others were not able to practice the instructions given.